Food Photography dan Eating Out di Media Sosial Instagram - Khoirun Nisak; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2017)
This study aimed to analyze influence of food photography towards eating out Sidoarjo community in instagram media. Data collection was done by using questionnaire to the respondents who visited the cafe/restaurant Mie akhirat, Kedai Kopi Medan, Wong Solo, dan Dapur M’riah that was located on Jalan Raya Ponti Gelanggang Olahraga Sidoarjo. Samples were taken through random sampling technique with total sample of 100 respondents. The result of this quantitative research showed that there was influence between food photography variable in social media instagram turns out to have an effect to the eating lifestyle of Sidoarjo community. The effect of food photography on eating out lifestyle was shown by R2 of 35.1%.